The effect of storage time and egg weight at room temperature on interior quality of hatching egg in Magelang duck - Fahri, Muhammad; Kurnianto, Edy; Suprijatna, Edjeng (Faculty of Animal Science, Universitas Brawijaya, 2019)
The objective of this study was to examine the effect of storage time and egg weight at room temperature on the interior quality of Magelang duck. The material used were 120 eggs of Magelang duck. The parameters observed were albumen index, egg yolk index and Haugh unit. The 4 x 3 factorial experiment with 2 factors was applied. In which the first factor (A) was the length of egg storage of: a1 = 1 day, a2 = 3 days, a3 = 5 days and a4 = 7 days and the second factor (B) was egg weight of b1 (low = 48,4g – 63,1g) b2 (medium = 63,2g – 73,6g) and b3 (high 73,7g - 81g,). The data were analyzed by the General Linear Model (GLM) procedure of Statistical Analysis System (SAS). The result showed that there was no interaction between storage time and egg weight on quality interior. Storage time was significant different (P<0,05) on albumin index, egg yolk index and Haugh unit. Egg weight had no effect on index albumen, egg yolk index and Haugh unit. In conclusion, the quality of the interior began to decline after being saved 3 days and the optimal egg weight for hatching eggs is medium egg weight.